The RING-H2 protein RNF11 is overexpressed in breast cancer and is a target of Smurf2 E3 ligase - Subramaniam, V (Nature Publishing Group, 2003)
The breast cancer-associated T2A10 clone was originally isolated from a cDNA library enriched for tumour messenger ribonucleic acids. Our survey of 125 microarrayed primary tumour tissues using affinity purified polyclonal antibodies has revealed that corresponding protein is overexpressed in invasive breast cancer and is weakly expressed in kidney and prostate tumours. Now known as RNF11, the gene encodes a RING-H2 domain and a PY motif, both of which mediate protein–protein interactions. In particular, the PPPPY sequence of RNF11 PY motif is identical to that of Smad7, which has been shown to bind to WW domains of Smurf2, an E3 ubiquitin ligase that mediates the ubiquitination and degradation of the TGFβ receptor complex. Using various mutants of RNF11 in GST pulldown and immunoprecipitation assays, we found that RNF11 interacts with Smurf2 through the PY motif, leading to ubiquitination of both proteins. Smurf2 plays an active role in the repression of TGFβ signalling, and our data indicate that overexpression of RNF11, through its interaction with Smurf2, can restore TGFβ responsiveness in transfected cells.